A New Infrared Probe Targeting Mitochondria via Regulation of Molecular Hydrophobicity - Sung, June; Rho, Jun Gi; Jeon, Gyeong G.; Chu, Yeonjeong; Min, Jun Sik; Lee, Sanghee; Kim, Jong H.; Kim, Wook; Kim, Eunha (Bioconjugate Chemistry, 2019)
Herein, we developed a near-infrared (NIR) fluorescent probe for mitochondrial staining based on the NIR fluorochrome, silicon-rhodamine. The hydrophobicity of the fluorescent core was systematically modified by conjugation with 10 different commercial amines. The resulting fluorescent compounds exhibited similar photophysical properties but diverse hydrophobicity. We identified the optimal level of hydrophobicity associated with high mitochondrial targeting efficiency. In particular, the SiR-Mito 8 probe provided excellent mitochondrial staining and successfully differentiated the live Hep3B cancer cells from normal L02 cells in vitro.
Keywords: Fluorescent cores; Fluorescent probes; Fluorochromes; Infrared probes; Mitochondrias; Molecular hydrophobicity; Near Infrared; Near-infrared; Near-infrared fluorescent; Rhodamine; Animals; Cell Line; Cell Line, Tumor; Fluorescent Dyes; HeLa Cells; Humans; Hydrophobic and Hydrophilic Interactions; Mice; Mitochondria; Optical Imaging; RAW 264.7 Cells; Rhodamines